General monographs and pharmacopoeial monographs of the State pharmacopoeia of Russian Federation XIII edition - V. A. Merkulov; E. I. Sakanyan; T. B. Shemeryankina; O. A. Mochikina; N. D. Bunyatyan (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The State Pharmacopoeia of the Russian Federation is a collection of general monographs and pharmacopoeial monographs. It should be reissued at least once in 5 years. The next scheduled edition of the State Pharmacopoeia of the Russian Federation is planned for publication in 2015. It will include both first developed in national and, in some cases, global pharmacopoeial analysis general and pharmacopoeial monographs, and updated revised general and pharmacopoeial monographs. The implementation of the general and pharmacopoeial monographs of the mentioned edition of the State Pharmacopoeia of the Russian Federation will significantly increase the level of national pharmacopoeial analysis and ensure its compliance with international standards.